2019
DOI: 10.1186/s13071-019-3532-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of water, sanitation and hygiene interventions in reducing soil-transmitted helminths: interpreting the evidence and identifying next steps

Abstract: The transmission soil transmitted helminths (STH) occurs via ingestion of or contact with infective stages present in soil contaminated with human faeces. It follows therefore that efforts to reduce faecal contamination of the environment should help to reduce risk of parasite exposure and improvements in water, sanitation and hygiene (WASH) are seen as essential for the long-term, sustainable control of STH. However, the link between WASH and STH is not always supported by the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 29 publications
4
56
1
5
Order By: Relevance
“…Children who reported always use of school drinking water were found to have lower odds of T. trichiura. Availability of drinking water to children especially when in school is key in controlling STH infections especially A. lumbricoides and T. trichiura since these infections are transmitted mainly through ingestion of contaminated food items like vegetables, fruits or drinking water [64]; this finding is consistent with other previous studies conducted among primary school children [8,32,65]. Children from households possessing assets such as television sets and electricity had lower odds of any STH infection.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 88%
“…Children who reported always use of school drinking water were found to have lower odds of T. trichiura. Availability of drinking water to children especially when in school is key in controlling STH infections especially A. lumbricoides and T. trichiura since these infections are transmitted mainly through ingestion of contaminated food items like vegetables, fruits or drinking water [64]; this finding is consistent with other previous studies conducted among primary school children [8,32,65]. Children from households possessing assets such as television sets and electricity had lower odds of any STH infection.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 88%
“…It is well established that chemotherapy alone will not break the transmission cycle. Recent studies have also shown that programmes solely focusing on WASH have limited effect on STH incidence and may provide no additional impact compared to mass drug administration programmes alone [32][33][34][35]. In contrast, health education and promotion programmes can be highly effective at reducing the incidence of STH infections if designed appropriately such as the highly successful "Magic Glasses" study, which resulted in a 50% reduction in STH infections [36].…”
Section: Discussionmentioning
confidence: 99%
“…Combining WASH and MDA interventions can potentially reduce multiple NTDs as a long-term sustainable solution for many Venezuelan communities. In addition to deworming, STH transmission routes can be narrowed through WASH interventions that create barriers for parasites [15] . This approach, however, requires an effective drug such as IVM that can interrupt transmission of multiple nematodes to prevent reinfection.…”
Section: Ivermectin To Enhance Wash-mda Integrated Approachesmentioning
confidence: 99%